Porównanie modeli propagacji fali akustycznej na przykładzie funkcjonowania Zakładu Unieszkodliwiania Odpadów w Ścinawce Dolnej = Comparison of acoustic wave propagation models on the example of functioning of the disposal works in Ścinawka Dolna - Szałata, Łukasz; Cuske, Mateusz; Godzwa, Adam (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper presents the methodology of acoustic wave propagation prediction for Waste Management Plant in Ścinawka Dolna. Modeling was performed in two different modeling programs: ZewHalas and LEQ Proffesional. Modeling carried out indicate that, despite the use of two different mathematical models, the results of the acoustic wave propagation are very similar.
Keywords: modelowanie hałasu; propagacja fali akustycznej; noise modeling; acoustic wave propagation